Development of the Industrial Sector as the Basis for the Growth of the Economy of the Russian Federation - V. I. Belov; D. A. Vasilevsky (Управленческое консультирование)
This article is devoted to the study of the problems and development prospects of the industrial production of Russia. In the current realities of the world economy, the study of the problems of industrial production (the fundamental basis of the Russian economy) is of particular importance. The research was conducted on three types of economic activity: «Mining», «Manufacturing Processes», «Production and distribution of electricity, gas and water». In the course of the research, statistical indicators were analyzed for the declared types of economic activity, actual problems were identified and key directions for the development of industrial production in the Russian Federation were identified. In addition, the article analyzed the return on assets of organizations, the profitability of goods sold and their impact on industrial production in the Russian Federation.